Արշակ Չոպանյանը Հայնրիխ Հայնեի մասին - Նազելի Մարգարյան (ՀՀ ԳԱԱ հրատ.)
В армянской литературе особое место занимает научно-филологическая и критическая деятельность видного писателя, публициста и общественного деятеля Аршака Чопаняна (1872–1954). А. Чопанян сотрудничал с журналами “Аревелк”, “Масис”, “Родина”. Был редактором выходившего в Париже журнала “Анаит”. Кроме исследований о великих деятелях армянской литературы А. Чопанян писал статьи, эссе также о западноевропейских (В. Гюго, О. Бальзак, Э. Золя, Г. Ибсен, Э. Верхарн) и русских (А. Пушкин, Н. Гоголь, И. Тургенев, Л. Толстой) писателях. Особое место занимает до сих пор малоизвестное исследование А. Чопаняна „Генрих Гейне“ в жанре эссе-портрета. The critical and scientific-philological activities of the prominent writer, publicist, journalist and public figure Arshak Chopanyan (1872–1954) has a significant place in Armenian literature. A. Chopanyan wrote and translated for the periodicals “Arevelk”, “Masis” , “Hairenik”. He worked as the editor of the journal “Anahit” being published in Paris. Together with publications about the great Armenian writers A. Chopanyan also wrote articles, essays about West-European (V. Hugo, O. Balzac, E. Zola, H. Ibsen, E. Verharn) and Russian (A. Pushkin, N. Gogol, I. Turgenev, L. Tolstoi) writers. Among these articles there is one (not so well-known) devoted to Heinrich Heine, written in essay-portrait genre.
Keywords: Biography; Literature; Auxiliary Sciences of History; Language and Literature